PENGATURAN ILLICIT ENRICHMENT DI INDONESIA - Miantoro, Bayu (Faculty of Law, Parahyangan Catholic University, 2020)
The United Nations Convention against Corruption (UNCAC) provides states with the opportunity, by means of their national criminal law, to criminalize a number of diverse corruptive behaviors, inter alia, illicit enrichment. By using a legal normative approach, the author discusses the chances and obstacles Indonesia face when introducing illicit enrichment as a crime alongside other crimes regulated in the Law on (the eradication of) corruption and law re. Money laundering. Apparently the primary aim to criminalize illicit enrichment through the national criminal law is to provide the state with a legal instrument to recover assets the result of corruption or money laundering. Attention should be given, however, on a number of obstacles coming from the interpretation of presumption of innocence principle and exiting regulation on the obligation for government officials to report their assets.